On a Subclass of Analytic Functions That Are Starlike with Respect to a Boundary Point Involving Exponential Function. (11th January 2022) - Lecko, Adam; Murugusundaramoorthy, Gangadharan; Sivasubramanian, Srikandan
Abstract : In the present exploration, the authors define and inspect a new class of functions that are regular in the unit disc D ≔ ς ∈ ℂ : ς < 1, by using an adapted version of the interesting analytic formula offered by Robertson (unexploited) for starlike functions with respect to a boundary point by subordinating to an exponential function. Examples of some new subclasses are presented. Initial coefficient estimates are specified, and the familiar Fekete-Szegö inequality is obtained. Differential subordinations concerning these newly demarcated subclasses are also established.